Love as a Contact Zone: Highland-Lowland Conflict and Negotiation in Three Philippine Cultural Texts - P. Pitlongay, Rachel (SARE: Southeast Asian Review of English, 2019)
This paper analyzes three Philippine cultural texts that depict highland-lowland romantic relationships with the aim of discovering how romantic discourse is appropriated to investigate the conflict and negotiation of culture. The texts examined are the short story “The Girl from Bauko” (Ablang 1988), the TV series Forevermore aired in 2014-2015 by a local Philippine TV station, and the 2006 film Don’t Give Up on Us. All three texts depict the blossoming romance between an Igorot, who is a member from an indigenous minority group, and a lowlander, whose collective ethnic identity is culturally dominant. To address these issues, this paper employs the concept of the “contact zone,” which is conceptualized here as a space where confrontation, exchange or kinship occurs or is developed. This paper argues that highland-lowland romantic relationships as depicted in the three narratives implicate and engage a range of issues such as the metropolis/periphery dichotomy, the romanticization of the highlander, and the prevalent socio-economic and ethnic divides.